2007
DOI: 10.1111/j.1752-7325.2007.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Dental Caries Development in 1.5‐Year‐Old High‐Risk Children in the Japanese Public Health Service

Abstract: The models could not predict caries risk but may be able to predict those cases who will not develop caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 16 publications
(32 reference statements)
4
22
1
1
Order By: Relevance
“…Although, there has been a significant overall decline in prevalence since the early 1970s worldwide, high disease levels have still been reported in a minority of individuals, labeled as high-caries risk individuals [5]. The distribution of caries level in certain populations is becoming increasingly skewed especially, in developing countries, which leads to the phenomena of disease polarization and increases the inequality in health [7,8]. Over time, a skewed distribution of caries prevalence has developed in many countries, with a minor proportion of 12-year-olds found with high or very high DMFT values [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although, there has been a significant overall decline in prevalence since the early 1970s worldwide, high disease levels have still been reported in a minority of individuals, labeled as high-caries risk individuals [5]. The distribution of caries level in certain populations is becoming increasingly skewed especially, in developing countries, which leads to the phenomena of disease polarization and increases the inequality in health [7,8]. Over time, a skewed distribution of caries prevalence has developed in many countries, with a minor proportion of 12-year-olds found with high or very high DMFT values [2].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies that adjust for tooth brushing indicate an association between greater consumption of sugars confectionery and greater risk of dental caries at 3.5 years and 18 months (Grindefjord et al, 1995;Grindefjord et al, 1996;Sakuma et al, 2007). The three other studies that adjust for tooth brushing indicate no significant association between consumption of sugars-sweetened food or sweet confectionery and dental caries (Grytten et al, 1988;Tada et al, 1999;Mariri et al, 2003).…”
Section: Sugars-sweetened Beverages and Bmimentioning
confidence: 97%
“…Seven cohort studies in eleven publications were identified that presented evidence on the relationship between sugars-containing beverage consumption and the incidence of dental caries in deciduous dentition in children, all of which adjusted their results for tooth brushing (Grytten et al, 1988;Grindefjord et al, 1995;Grindefjord et al, 1996;Tada et al, 1999;Levy et al, 2003;Mariri et al, 2003;Sakuma et al, 2007;Ismail et al, 2008;Warren et al, 2008;Lim et al, 2008;Ismail et al, 2009). Three cohorts were reported in more than one publication: (Grindefjord et al, 1995;Grindefjord et al, 1996) reported on one cohort; Lim et al, 2008;Ismail et al, 2009) reported on one cohort; and (Mariri et al, 2003;Levy et al, 2003) reported on one cohort.…”
Section: Sugars-sweetened Beverages and Bmimentioning
confidence: 99%
See 2 more Smart Citations